2017
DOI: 10.1002/jsfa.8703
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a thermostable recombinant l‐rhamnose isomerase from Caldicellulosiruptor obsidiansis OB47 and its application for the production of l‐fructose and l‐rhamnulose

Abstract: The recombinant L-RI could effectively catalyze the formation of l-rhamnulose and l-fructose, suggesting that it was a promising candidate for industrial production of l-rhamnulose and l-fructose. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The optimal temperature and pH using dextran T‐2000 as a substrate were at 55 °C and pH 5.0, respectively. In the present study, the recombinant DEX enzyme exhibited high activity under weak acidic conditions, which may decrease nonspecific reactions and the accumulation of undesirable byproducts that could be accrued under the alkaline conditions typically employed in the sugar industry [23] …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The optimal temperature and pH using dextran T‐2000 as a substrate were at 55 °C and pH 5.0, respectively. In the present study, the recombinant DEX enzyme exhibited high activity under weak acidic conditions, which may decrease nonspecific reactions and the accumulation of undesirable byproducts that could be accrued under the alkaline conditions typically employed in the sugar industry [23] …”
Section: Resultsmentioning
confidence: 86%
“…In the present study, the recombinant DEX enzyme exhibited high activity under weak acidic conditions, which may decrease nonspecific reactions and the accumulation of undesirable byproducts that could be accrued under the alkaline conditions typically employed in the sugar industry. [23] Temperature stability is generally considered to be one of the primary factors determining whether an enzyme is suitable for industrial applications. [24] Herein, the recombinant enzyme retained 90.14, 88.27 and 71.36 % of initial activity after incubation at 40, 45 and 50°C for 60 min, respectively ( Figure 3C), but this decreased markedly following incubation above 55°C.…”
Section: Effects Of Temperature and Ph On Dextranase Activity And Stamentioning
confidence: 99%
“…The plasmid harboring the C. obsidiansis OB47 L-RI gene was constructed in our previous work. 27 The reagents used for sitedirected mutagenesis of wild-type L-RI gene were obtained from Generay Biotech Company, Ltd. Isopropyl-β-D-1-thiogalactopyranoside (IPTG) for induction was from Sigma. The Ni 2+ -chelating affinity-chromatography resin was provided by GE.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The biological production of L-rhamnulose by L-RhI from C. obsidiansis OB47 suggested that the different substrate concentrations exhibited influence on conversion. The higher concentration that led to lower conversion with time elapsing might be due to the product inhibition [4]. Aldose-ketose isomerization by the enzymatic method is reversible, and its reaction equilibrium is unfavorable for ketose formation [5].…”
Section: Bioconversion Of L-rhamnose Into L-rhamnulose By Osrpibmentioning
confidence: 99%
“…L-Rhamnulose (6-deoxy-L-fructose), as one of the rare deoxy ketoses, is widely used in the food industry. As a starting material for preparing food flavors, it has been used widely because of its caramel-like aroma [4]. Moreover, it can be directly isomerized or epimerized into other rare sugars [5].…”
Section: Introductionmentioning
confidence: 99%